Nurturing an identity of land custodianship of young people through a biodiversity learning programme: The Moletele Youth Learning Programme - Mponwana, William Oupa (Rhodes University, Faculty of Education, Department of Education)
This study was an exploration of value creation through scaffolding in a context specific learning programme with young people within the Moletele Communal Property Association (CPA) who own land through the land reform programme in South Africa. The study aimed to support the development the identity of land custodianship amongst young people by developing their skills and competencies in a situated learning context. The study also informed ongoing support work through the RESILIM-O resilience building project implemented by the Association for Water and Rural Development (AWARD) to help the Moletele Community Property Association to better understand the implications of biodiversity and land use for developing sustainable beneficiation projects and planning. A case study approach was adopted through a learning programme with young people as an in-depth exploration of the complexities of land and biodiversity. Data were collected during sessions in the learning programme where we used a spiral framework to facilitate learning focusing on four themes for primary data: knowledge competence, technical skills, self-organization and collective agency which are linked to building an identity of custodianship. Semi structured interviews were conducted at the end of the learning programme as a secondary data source. The study found that scaffolding remained an important process throughout the learning programme, and different types of scaffolding was needed to support the learning processes and themes. Furthermore, different types of value were created over time through the interactions and activities of the learning programme. The study also found that young people have a desire to participate in their communal property association. Lastly the study revealed that building custodianship as an identity is a continuous, long term process that needs commitment of time, resources and supportive learning processes, for an identity of custodianship to emerge.
Keywords: Sustainable biodiversity -- South Africa -- Mopani District Municipality; Association for Water and Rural Development (South Africa); Land reform beneficiaries -- South Africa -- Mopani District Municipality; Agricultural development projects -- South Africa -- Mopani District Municipality; Land use-- Study and teaching -- South Africa -- Mopani District Municipality; Identity (Psychology) Social aspects -- South Africa -- Mopani District Municipality; Identity (Psychology) in youth -- South Africa -- Mopani District Municipality; Moletele Youth Learning Programme; Moletele Communal Property Association (CPA); RESILIM-O